2013
DOI: 10.1016/j.scr.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and in vitro culture of porcine spermatogonial germ cells in low temperature culture conditions

Abstract: The objective of this study was to establish a porcine spermatogonial germ cell (pSGC) line and develop an in vitro culture system. Isolated total testicular cells (TTCs) from 5-day-old porcine testes were primary cultured at 31, 34, and 37°C. Although the time of colony appearance was delayed at 31°C, strong alkaline phosphatase staining, expressions of pluripotency marker genes such as OCT4, NANOG, and THY1, and the gene expressions of the undifferentiated germ cell markers PLZF and protein gene product 9.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 52 publications
3
60
0
Order By: Relevance
“…Goel et al (2007) maintained isolated porcine gonocytes for 7 days in DMEM/F12 containing 10% serum, while more recently, Zheng et al (2013) incubated piglet SSCs with different serum concentrations and growth factors, with a primary culture time of 10 days. Previous research has shown that it is possible to maintain porcine SSCs for 60 days at 31°C (Lee et al, 2013). In the present work, Bama mini-pig SSCs were cultured in serum-free medium for at least 100 days and passaged over 20 times, while immunocytochemistry revealed cell clusters to be positive for DBA, UCHL1, and CDH1, confirming them to be comprised of SSCs.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Goel et al (2007) maintained isolated porcine gonocytes for 7 days in DMEM/F12 containing 10% serum, while more recently, Zheng et al (2013) incubated piglet SSCs with different serum concentrations and growth factors, with a primary culture time of 10 days. Previous research has shown that it is possible to maintain porcine SSCs for 60 days at 31°C (Lee et al, 2013). In the present work, Bama mini-pig SSCs were cultured in serum-free medium for at least 100 days and passaged over 20 times, while immunocytochemistry revealed cell clusters to be positive for DBA, UCHL1, and CDH1, confirming them to be comprised of SSCs.…”
Section: Discussionsupporting
confidence: 70%
“…Buffalo SSCs have been cultured in vitro (Kala et al, 2012). while in 2013, the in vitro proliferation of porcine SSCs for 60 days at 31°C was reported (Lee et al, 2013). Mouse SSCs can be multiplied in medium supplemented with Knockout Serum Replacement (Aoshima et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the established cell lines could be cultured in a wide range of culture temperatures from 24 to 30°C even though significant high cell growth was observed in 28 and 30°C conditions. Culture in various temperatures may have a potential merit as feeder cells because co-culture with germline stem cells may require a different optimal culture temperature as in the case of mammalian species (Lee et al, 2013). In addition, the results showed that 15 % FBS also induced significant high cell growth at a similar level with 20 % FBS in the ABG3 and ABG5 lines, suggesting that the application of a cell line-specific protocol can save overall cost by diminishing the use of high-cost FBS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high application possibilities to animal transgenic research as a mediator conveying new traits to the next generation, lots of trials for in vitro culture and manipulation of them have been conducted in many mammalian (Guan et al, 2006;Aponte et al, 2008;Lee et al, 2013;Tiptanavattana et al, 2013;Lee et al, 2014) and some avian species (Park et al, 2008;Song et al, 2014). In fish, similar studies have been performed in small fish models (Sakai, 2002;Hong et al, 2004;Fan et al, 2008;Kawasaki et al, 2012;Li et al, 2014), but the related ones dealing with large farmed fish have been rarely conducted (Shikina et al, 2008;Shikina and Yoshizaki, 2010;Lacerda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…of the production of transgenic mice using isolated spermatogonial stem cells (Brinster and Zimmermann, 1994), SSC research has advanced significantly. SSCs have been isolated and characterized in many species, including mice (Nagano et al, 1998), rats (Ryu et al, 2007), pigs (Lee et al, 2013b), and non-human primates (Hermann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%